AN ANALYSIS OF DEPRECIATION TAX SHIELD ON PROPERTY AND REAL ESTATES INDUSTRY IN INDONESIA - Nurul Izzah Lubis (LPPM Univ Potensi Utama, 2019)
Depreciation Tax Shield is a tax protection from depreciation expenses that can be used to reduce the company's profits so that the tax burden paid is lower than it should be. The depreciation tax shield can be calculated with total depreciation multiplied by the effective tax rate (ETR). This DTS then affects taxable income (TI) which is obtained from EBITDA multiplied by ETR. After that, net income (NI) can be calculated, namely by reducing EBITDA from IT. The final step is to add back the depreciation tax shield (DTS) to the Cash Flow (CF) by adding DTS and NI to find out how much tax evasion is done by the company. This study aims to test and analyze the depreciation tax shield by taking the place of research and complete financial report data, namely from 45 Property and Real Estates companies listed on the Indonesia Stock Exchange for 2015-2017. The data analysis technique used is descriptive statistics and depreciation tax shield analysis. The results of this study indicate that the depreciation tax shield looks to increase from 2015 by 12% in 2016 and increases to 30% in 2017 so it can be concluded that the Property and Real Estates companies listed on the Indonesia Stock Exchange utilize investment assets and property to minimize profits and tax burden.